A precise photometric ratio via laser excitation of the sodium layer – II. Two-photon excitation using lasers detuned from 589.16 and 819.71 nm resonances. Issue 3 (7th June 2021) - Albert, Justin E; Budker, Dmitry; Chance, Kelly; Gordon, Iouli E; Bustos, Felipe Pedreros; Pospelov, Maxim; Rochester, Simon M; Sadeghpour, H R
ABSTRACT: This paper is the second in a pair of papers on the topic of the generation of a two-colour artificial star [which we term a laser photometric ratio star (LPRS)] of de-excitation light from neutral sodium atoms in the mesosphere, for use in precision telescopic measurements in astronomy and atmospheric physics, and more specifically for the calibration of measurements of dark energy using type Ia supernovae. The two techniques, respectively, described in both this and the previous paper would each generate an LPRS with a precisely 1:1 ratio of yellow (589/590 nm) photons to near-infrared (819/820 nm) photons produced in the mesosphere. Both techniques would provide novel mechanisms for establishing a spectrophotometric calibration ratio of unprecedented precision, from above most of Earth's atmosphere, for upcoming telescopic observations across astronomy and atmospheric physics; thus greatly improving the performance of upcoming measurements of dark energy parameters using type Ia supernovae. The technique described in this paper has the advantage of producing a much brighter (specifically, brighter by approximately a factor of 10 3 ) LPRS, using lower power (≤30 W average power) lasers, than the technique using a single 500 W average power laser described in the first paper of this pair. However, the technique described here would require polarization filters to be installed into the telescope camera in order to sufficiently remove laser atmospheric Rayleigh backscatter from telescope images, whereas the technique described in the first paper would only require more typical wavelength filters in order to sufficiently remove laser Rayleigh backscatter.